Should the chiropractic profession embrace the doctrine of informed consent? - Lehman, James J. (Elsevier, 2008)
This commentary provides a narrative review of the literature focusing on the use of a health care informed consent process in the United States. This article reviews the current positions of the World Medical Association, American Medical Association, American Chiropractic Association, Wisconsin and New Jersey State Courts, US Federal Government Office of Health Policy and Clinical Outcomes, and 1 college of chiropractic regarding the doctrine of informed consent. The authors recommend that the chiropractic profession embrace the doctrine of informed consent and promulgate it as a standard of care. The implementation of this doctrine by chiropractic physicians promotes and improves the safety of chiropractic interventions.